The impact of middle management commitment on improvement initiatives in public organisations. Issue 5 (5th September 2016) - Alhaqbani, Abdullah; Reed, Deborah M; Savage, Barbara; Ries, Jana
Abstract : Purpose: Top management commitment is considered a significant factor in improvement programmes, and many papers have been written about the role of top management commitment in implementing a quality management system. However, not considering other management levels' commitment, such as middle management, may lead to issues in achieving organisational development. Public organisations that work through vertical structures may face a lack of middle management commitment, which might have a negative impact on lower and non-management staff commitment to improvement programmes. In this regard, this study seeks to examine the impact of middle management's commitment towards improvement initiatives in public organisations Design/methodology/approach: Empirical research with a mixed-method design used semi-structured interviews and a questionnaire to explore the current practices of continuous improvement (CI) and examine employees' views from different management levels of the implications of current improvements in a Saudi public service organisation Findings: The analysis indicated that the lower managers and non-management staff agree that, after the implementation of the quality management system, the organisation's middle management showed a lack of commitment to that system. Moreover, this lack of commitment is recognised in the analysis of participants' views of CI practices recorded in the questionnaire and interviews. This lack of commitment has caused poor employee commitment and thus a lack of problem solving in organisational departments. It is also responsible for a lack of employee involvement, the centralisation of decisions, deficiencies in terms of determining and applying training, inequality between employees and a lack of trust between employees and their managers. These issues could be managed and resolved through middle management and their commitment. Practical implications: Increasing middle managers' awareness of the importance of their commitment to improvement initiatives can have an impact on employees' commitment towards improvement initiatives, especially in those public organisations that have vertical/hierarchical structures. The level of commitment towards the implementation of improvement programmes needs further in-depth analyses to identify which factors influence public organisation leaders' commitment to improvement programmes. Originality/value: The results of this study could motivate middle managers in public organisations to review their policies and to facilitate continuous improvement initiatives.